2006
DOI: 10.1007/s00417-006-0462-8
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral canaliculitis following SmartPLUG insertion for dry eye syndrome post LASIK surgery

Abstract: To the best of our knowledge, this is the first report of bilateral canaliculitis following intra-canalicular SmartPLUG insertion. This case illustrates that punctal occlusion with the newer generation intra-canalicular plugs carries a risk of canaliculitis and that irrigation is not always effective in removing these devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 10 publications
(20 reference statements)
0
13
0
Order By: Relevance
“…On the other hand, a few studies reported that canaliculitis and dacryocystitis have been seen in these plug therapy [17,18], but in this study, in a single case, the pyogenic granuloma was observed at the end of the 1st year. There were few studies reported several complications such as canaliculitis, dacryocystitis, and pyogenic granuloma [13,[17][18][19].…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…On the other hand, a few studies reported that canaliculitis and dacryocystitis have been seen in these plug therapy [17,18], but in this study, in a single case, the pyogenic granuloma was observed at the end of the 1st year. There were few studies reported several complications such as canaliculitis, dacryocystitis, and pyogenic granuloma [13,[17][18][19].…”
Section: Discussionmentioning
confidence: 45%
“…There were few studies reported several complications such as canaliculitis, dacryocystitis, and pyogenic granuloma [13,[17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of extrusion is lower for a modified punctal plug, the Flex Plug Ò (Eagle Vision), which is retained longer than the Eagle Plug [20]; this may be beneficial when treating dry eye signs and symptoms over longer periods. Other options may be intracanallicular plugs, for example collagen plugs, which are retained in the lacrimal canaliclaris for several weeks, and the semi-permanent SmartPLUG TM [21]. These plugs are especially suitable for patients who complain of foreign body sensation with the silicon plugs.…”
Section: Discussionmentioning
confidence: 97%
“…2,3 It is often misdiagnosed 4 leading to a delay in diagnosis. 5 Canaliculitis is generally a unilateral condition.…”
Section: Introductionmentioning
confidence: 99%
“…6,8 Additional findings with cases of secondary canaliculitis include an inflammatory mass projecting from the punctum or intermittent blood-stained tears. 2,3,8 Canaliculitis should be considered as a possible etiology with persistent or recurrent eyelid lesions, chalazia, or abscesses. 9 A primary infection of the lacrimal canaliculus is relatively uncommon.…”
Section: Introductionmentioning
confidence: 99%